Cooperative Behaviors in Group-Living Spider Mites - Schausberger, Peter; Yano, Shuichi; Sato, Yukie (Frontiers in Ecology and Evolution, 2021)
Cooperative behaviors are evolutionary stable if the direct and/or indirect fitness benefits exceed the costs of helping. Here we discuss cooperation and behaviors akin to cooperation in subsocial group-living species of two genera of herbivorous spider mites (Tetranychidae), i.e., the largely polyphagous Tetranychus spp. and the nest-building Stigmaeopsis spp., which are specialized on grasses, such as bamboo. These spider mites are distributed in patches on various spatial scales, that is, within and among leaves of individual host plants and among individual hosts of single or multiple plant species. Group-living of spider mites is brought about by plant-colonizing foundresses ovipositing at local feeding sites and natal site fidelity, and by multiple individuals aggregating in the same site in response to direct and/or indirect cues, many of which are associated with webbing. In the case of the former, emerging patches are often composed of genetically closely related individuals, while in the case of the latter, local patches may consist of kin of various degrees and/or non-kin and even heterospecific spider mites. We describe and discuss ultimate and proximate aspects of cooperation by spider mites in host plant colonization and exploitation, dispersal, anti-predator behavior, and nesting-associated behaviors and conclude with theoretical and practical considerations of future research on cooperation in these highly rewarding model animals.